Modelo dinâmico de estimativa da evaporação da água em solo não-estratificado e sem vegetação - C Sediyama, Gilberto; de A Carvalho, Sérgio Marcos; Ferreira, Paulo Afonso; Bernardo, Salassier (Revista Ceres, 2025)
In this study, a dynamic soil water evaporation model for estimating the daily water evaporation rate from bare soil exposed to natural weather was used and tested under field conditions.